Assessment of the external debt impact on a country’s economic development indicators: Evidence from Ukraine - Yuriy Petrushenko; Maxim Korneyev; Natalia Nebaba; Olena Banchuk-Petrosova; Anna Bohorodytska (Investment Management & Financial Innovations, 2022)
External public debt is not only a means of raising funds to finance public needs, but also an effective tool for stabilizing a country`s economic development, the assessment and analysis of which allows making effective management decisions at the state level and developing effective measures to improve the economic and debt situation. The paper aims to assess the impact of external public debt on Ukraine’s economic development indicators (GDP, foreign direct investment, foreign exchange reserves). In order to achieve the stated goal distributed lag models are used, which allow modeling a country’s economic development (according to key indicators) within certain forecast scenarios. The study covers the period from 2009 to 2021. An analysis of the dynamics of external public debt in Ukraine led to the conclusion about the unstable debt situation in Ukraine and a significant increase in external debt in recent years. Econometric models with a distributed lag of three years are built and the results of the influence of external public debt in different time periods are analyzed. The average lag in the built models is about one and a half years (for GDP) and two and a half years (for foreign direct investment). This value indicates that the average change (increase/decrease) in external public debt will change economic development over time. A positive conclusion is made on the possibility of not only assessing the time lag between the indicators, but also on the prospects for forecasting both the public debt and key indicators of Ukraine`s economic development. AcknowledgmentThe article was published as part of research projects “Convergence of economic and educational transformations in the digital society: modeling the impact on regional and national security” (No. 0121U109553) and “Reforming the lifelong learning system in Ukraine for the prevention of the labor emigration: a coopetition model of institutional partnership” (No. 0120U102001).